HUMAN CAPITAL DEVELOPMENT AND THE MANAGEMENT OF UNEMPLOYMENT CRISES IN NIGERIA - Sowho, P O; Abubaka, T O; Uba, U O (Sokoto Educational Review, 2017)
Unemployment is a condition whereby the able-bodied men and women who are qualified and ready to work do not have commensurate work to do. In Nigeria it has developed to a crises situation as the unemployment now affect both the graduates and non-graduates alike which is principally blamed on mismatch between the skills acquired in institutions of learning and the country labour market needs. This calls for question on the type of education system and the constituents of human capital formation in Nigeria. The paper therefore concluded that the rate of unemployment in Nigeria will continue to increase manifest in multidimensional problem to the economy and the entire social fabrics of the national life if the system of education fails to evolve talents and skills that will use materials resources to develop technology which will be compliant with human potentials. Based on this, the researchers recommended among others that the school curriculum should be review in line with societal demand pattern, education system that will focus on developing indigenous technology and avoid waste of manpower.